The Effect of First Aid Training on Accidents (PPPK) on Knowledge of Fracture Handling of the “Pagar Nusa” Pencak Silat Trainer in Semanding District - Suhartono Suhartono; Novia Dwi Astuti (Alliance oh Health Activists (AloHA), 2020)
Martial arts sports (body contact) have a very high risk of injury. This is due to several causes of injury, including fractures in both the upper and lower extremities. The purpose of this study was to determine the effect of first aid training on accidents (P3K) on knowledge of fracture handling of the pencak silat trainer